Analysis of Service Quality, Customer Satisfaction, Brand Image, and Market Share on Passenger Loyalty - Alfais Amin Darmawan (Siber International Journal of Digital Business (SIJDB), 2024)
Literature review articles related to the analysis of service quality, customer satisfaction, brand image and market share on ship passenger loyalty are scientific literature articles in the scope of marketing management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. Data were obtained from previous studies that are relevant to this study and sourced from academic online media such as the Scopus Emerald Journal, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital books. The results of this article are: 1) Service Quality affects Ship Passenger Loyalty; 2) Customer Satisfaction affects Ship Passenger Loyalty; 3) Brand Image affects Ship Passenger Loyalty; and 4) Market Share affects Ship Passenger Loyalty.